A christmas carol - Zaki, Zaki Saied; ESC Creative Department ([Cairo] Educational Services Company, 2024)
Follws the transformative journey of Ebenezer Scrooge as the bitter and cold-hearted old man is visited by supernatural beings, through haunting encounters with ghosts of christmas past, present, and future, scrooge's icy facade begins to melt, revealing the depths of his humanity, dive into this timeless tale of self-discovery, second chances, and the transcendent power of love that scrooge unravels throughout the story
English Stories
Keywords: English stories